Elucidating impacts of partitioning and transmembrane permeability on absorption of chemicals in human gastrointestinal tract - Shenghong Wang; Zhizhen Zhang; Dingsheng Li; Li Li (Environment International)
Estimating the fraction absorbed (Fabs) of orally ingested chemicals in the human gastrointestinal tract is pivotal for assessing chemical concentrations in the systemic circulation and informing potential toxicological impacts, especially in the era of “new approach methods” targeting chemical screening and prioritization. Here, we present an input-parsimonious and computationally efficient approach to support the screening-level estimation of Fabs from partitioning (characterized using the octanol–water partition coefficient at pH 7.4, KOW) and transmembrane permeability (characterized using the Caco-2 apparent permeability, Papp,Caco-2), based on a mechanistic description of processes involved in chemical absorption:Fabs=1-e-164571-2.40×10-9+2.40×10-9∙KOW∙10.0075∙1Papp,Caco-2-10.001530.346+10.00115Our approach demonstrates satisfactory performance in predicting Fabs for 176 hydrophobic and hydrophilic organic chemicals, with a Pearson correlation coefficient greater than 0.75 and a root mean square error of approximately 15 % in absolute Fabs values between experimental measurements and predictions. Our results show that the Fabs of highly hydrophobic chemicals (KOW > 108) are closely dependent on partitioning, whereas the Fabs of relatively hydrophilic chemicals (KOW < 106) are sensitive to transmembrane permeability. We also demonstrate that transmembrane permeability and partitioning are not interdependent, and both should be treated as fundamental chemical properties in predicting Fabs.